The effects of the coach-athlete working alliance on affect and burnout among high level coaches - Myhre, K.; Moen, F. (Central European Journal of Sport Sciences and Medicine, 2017)
Research suggests that the numbers of coaches who are suffering from burnout symptoms are considerably high among coaches in elite sport. In this study, the authors explore the effects of the coach-athlete working alliance on positive- and negative affect and burnout in a group of high-level coaches. An online survey, consisting of the Working Alliance Inventory-Short Version, the Positive and Negative Affect Schedule and the Maslach Burnout Inventory, was completed by a sample of 299 coaches working with elite athletes or junior elite athletes. Data analysis was conducted using structural equation modelling. The model explained 57% of the variance in cynicism, 32% of the variance in reduced sense of accomplishment and 26% of the variance in exhaustion. These effects mainly derived from positive affect and negative affect. However, working alliance showed a significant indirect effect on all three dimensions of burnot through the mediating variables positive affect and negative affect. These results are discussed in a cognitive activation-perspective.